MELD score exception overemphasizes the benefits to hepatocellular carcinoma patients in transplant. A proposal to improve the rules - Agnaldo Soares Lima; Nathália Nunes Godinho Lopes; Bárbara Buitrago Pereira; Leandro Ricardo Navarro Amado (Brazilian Journal of Transplantation, 2017)
Purpose: In Model for End-stage Liver Disease (MELD)-based allocation systems patients with cancer and some other diseases are assigned a special score. The goal of this study was to assess the fairness of organ distribution by the MELD system among different groups of diseases. Methods: Retrospective study with adult patients between 2009 and 2013. Demographics and MELD scores were compared with the incidence of transplant or death, patient origin and disease groups. Results: 260 selected patients were submitted to transplant or died before the transplant. Their median age was 54.9 years (12.1 -73.9 years); 70.4% were men; 63.3% had chronic liver diseases (alcoholic cirrhosis 33.1%, C-virus cirrhosis 24.2%). Exception score was assigned to 26.5% of listed patients. These patients received 31% of transplanted organs and had lower pre-transplant mortality or dropout (14.2 times less) rates than the other patients (p <0.001). Receiving exception points resulted in a higher likelihood of being transplanted. Conclusion: The authors propose the use of a regional variable score for transplantation in special situations, which should be based on the median MELD score of the latest transplants for chronic liver diseases, to refrain from harming patients who have access to transplant according to the calculated MELD score.